Values, intercultural sensitivity, and uncertainty management: a cross-cultural investigation of motivational profiles - Kim, Jungsun; Kim, Huai-Rhin (Frontiers in Psychology, 2025)
IntroductionPersonal values function as core motivational forces shaping cognition and behavior. However, the interaction between these values, intercultural sensitivity, and intolerance of uncertainty across cultures has received limited empirical attention. This study investigates how these constructs combine to form distinct motivational profiles among university students in South Korea and the United States.MethodsUsing a person-centered latent profile analysis (LPA), we identified value configurations among South Korean (N = 517) and U.S. (N = 431) undergraduates. Participants completed the Portrait Values Questionnaire–Revised Revised (PVQ-RR), Intercultural Sensitivity Scale (ISS), and Intolerance of Uncertainty Scale–Short Form (IUS-12). Multinomial logistic regression identified predictors of profile membership.ResultsAmong Korean students, five value profiles emerged: Integrative Traditionalists (41%), Low Tradition Endorsement (24.2%), Change-Oriented (21.1%), Low Tradition/High Openness (17.5%), and Tradition-Oriented (21.8%). The U.S. sample revealed four profiles: Growth-Oriented (24.8%), Broad Value Endorsement (21.8%), Security-Focused (35.0%), and Low Tradition Endorsement (18.3%). Across both samples, higher intercultural engagement and confidence predicted membership in growth-oriented profiles, while elevated inhibitory intolerance of uncertainty and lower engagement characterized tradition- or security-focused profiles. Gender effects appeared only in Korea, where women demonstrated greater likelihood of belonging to tradition-oriented groups.DiscussionThese findings challenge assumptions about the incompatibility between tradition and openness values in Schwartz’s framework. Cultural tightness and individual psychological dispositions appear to jointly shape motivational value integration. The results have implications for designing culturally responsive interventions that enhance intercultural competence and promote adaptive value systems in diverse educational settings.